2009
DOI: 10.1161/circep.108.797944
|View full text |Cite
|
Sign up to set email alerts
|

Left Atrial Posterior Wall Isolation Does Not Improve the Outcome of Circumferential Pulmonary Vein Ablation for Atrial Fibrillation

Abstract: Background-Ablation of the pulmonary veins (PVs) for atrial fibrillation treatment is often combined with linear radiofrequency lesions along the left atrium (LA) to improve the success rate. The study was designed to assess the contribution of LA posterior wall isolation to the outcome of circumferential pulmonary vein ablation (CPVA). Methods and Results-CPVA consisted of continuous radiofrequency lesions encircling both ipsilateral PVs plus an ablation line along the mitral isthmus. Patients were then rando… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
125
1
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 140 publications
(130 citation statements)
references
References 44 publications
1
125
1
3
Order By: Relevance
“…These results suggest that antral ablation already targets the critical points of the LA posterior wall capable of triggering and sustaining arrhythmias and thus no further lesion lines are required. However, permanent isolation of the posterior wall was not proven in the study by Tamborero et al 47 In fact, all patients undergoing repeat procedures showed absence of posterior wall isolation and gaps along the box lesions.…”
Section: Total (95% Ci)mentioning
confidence: 90%
See 1 more Smart Citation
“…These results suggest that antral ablation already targets the critical points of the LA posterior wall capable of triggering and sustaining arrhythmias and thus no further lesion lines are required. However, permanent isolation of the posterior wall was not proven in the study by Tamborero et al 47 In fact, all patients undergoing repeat procedures showed absence of posterior wall isolation and gaps along the box lesions.…”
Section: Total (95% Ci)mentioning
confidence: 90%
“…A study performed by Tamborero et al, 47 which assessed the benefit of a box lesion in the LA posterior wall in patients undergoing transcatheter radiofrequency AF ablation, did not detect a better outcome of WACA PVI plus posterior box versus WACA PVI alone. These results suggest that antral ablation already targets the critical points of the LA posterior wall capable of triggering and sustaining arrhythmias and thus no further lesion lines are required.…”
Section: Total (95% Ci)mentioning
confidence: 92%
“…527 The recently published BELIEF trial reported at 28% efficacy of an extensive ablation strategy, including ablation of the posterior wall, in patients with long-standing persistent AF. 528,529 A survey of the writing group shows that 15% of the writing group members perform posterior wall isolation in patients with PAF during an initial AF ablation procedure, and 18% isolate the posterior wall during a repeat ablation procedure in a patient with PAF.…”
Section: Section 5: Strategies Techniques and Endpointsmentioning
confidence: 99%
“…Of note, part of these lines were made on an anatomic basis without verifying that conduction block had indeed been established. Whether additional lesions during either CA or SA would be beneficial for specific patient populations remains to be determined 24,25 ; this study was not designed or powered to answer that question.…”
Section: Procedural Effects Of Sa and Camentioning
confidence: 99%